PENGARUH AUDIT FEE, AUDIT TENURE, AUDIT DELAY DAN AUDITOR SWITCHING TERHADAP PEMBERIAN OPINI AUDIT: (Studi Empiris Pada Perusahaan Jasa Sektor Keuangan Yang Terdaftar di BEI Tahun 2017-2021) - Reza Maulana; Anisa Anisa (Jurnal Ilmiah Akuntansi, 2024)
The aim of this research is to a fundamental comprehension of the process by which an audit opinion is rendered and the various determinants that impact it. Quantitative research presents audited annual financial reports, which are accessible on the website of the Indonesia Stock Exchange (BEI), utilizing precise secondary data. The study analyzed financial services sector entities that were registered on the IDX between the years 2017 and 2021. A total of 63 entrepreneurs were intentionally selected using the purposive sampling technique over the course of the five-year research period. collected information. The Eviews 9 application is utilized to conduct logistic regression analysis as the data analysis method for this study. Concurrently, the findings of this study indicate that audit tenure, audit fees, audit delay, auditor switching, and audit delay all impact the provision of audit opinions. Moreover, a straightforward conclusion can be drawn: audit fees and audit delay do affect audit opinion, whereas audit tenure and auditor switching do not.